Areview On Rheumatoid Arthiritis - Sumathi, Lalitha; Pichaivel, Manimekalai; ., Sabarinath; Kandasamy, Thilagasundari (Asian Journal of Pharmaceutical Research and Development, 2022)
Rheumatoid arthritis is a persistent, painful inflammatory condition characterized by serious destruction of the bone marrow and cartilage in the joints. It can also affect the body as a whole, including the tissues, leading to disorders of the heart, lungs, nervous system, and eyes. It is an extremely painful inflammatory condition that significantly limits movement due to pain and joint deterioration. Systemic disease rheumatoid arthritis usually affects tissues that constrict. Age, race, inheritance, aberrant immunological functioning, and stress are risk factors. Early rheumatoid arthritis appears to have a unique cytokine profile for the production of interleukin-4, 13, and 15,52, which later show in chronic rheumatoid arthritis. The main objectives of rheumatoid arthritis treatment are to minimize pain and stop or slow the disease’s progression. Therefore, early disease detection and correct diagnosis and treatment are crucial. Low-dose GCs combined with Awards are a safe and effective therapy choice for radiographic progression, symptom reduction, and high rates of clinical remission.